Assessment of the point of no return in choice reaction time under uncertainty conditions in basketball pass - Quílez Maimón, A.; Rojas Ruiz, F. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The purposes of this study in basketball pass were to analyse how uncertainty affects Reaction Times (RT) and to assess the Point of No Return (PoNR) in choice reaction times. 10 experienced basketball players participated. LEDs lights projected targets on screens. As LED was on, participants hit the target as fast as possible to measure their RT. In the second phase and during the pass Movement Time (MT), the target position could randomly shift to another spot at five instants with progressive delays depending on RT & MT of each player. Results showed that uncertainty increases RT, but does not affect MT. As target change was delayed, neither RT nor MT changed but errors appeared. 2/5MT+RT defined PoNR, as errors soared from this point onwards. Further work is suggested to increase the study external validity and to define a training procedure to decrease both RTs & errors under uncertainty conditions.